Pengabdian Kolaboratif dalam Pengelolaan Aset Badan Pengelolaan Keuangan dan Aset Daerah - Masruroh, Nikmatul; Ferdianto; Nelly Septya Agus Salim; Nafiah Nur Andini (Insan Kreasi Media, 2024)
This service is a collaboration between students and lecturers of UIN KHAS Jember and BPKAD in creating an effective asset management model. This service aims to tabulate and reorganize the list of assets owned by the Jember Regency Government and aims to provide education to the public about regional assets. This is due to the existence of many Jember Government assets, so a systematic asset management process is needed. This service uses a collaborative method of two institutions, namely UIN Kiai Haji Achmad Siddiq Jember together with BPKAD to manage assets in the Jember Regency Government. This service produces a systematic asset management model starting from planning, authorization and evaluation processes. as well as public understanding of local government assets.